Proceedings of the 2nd ACM SIGOPS/EuroSys European Conference on Computer Systems 2007 2007
DOI: 10.1145/1272996.1273026
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control of virtualized resources in utility computing environments

Abstract: Data centers are often under-utilized due to over-provisioning as well as time-varying resource demands of typical enterprise applications. One approach to increase resource utilization is to consolidate applications in a shared infrastructure using virtualization. Meeting application-level quality of service (QoS) goals becomes a challenge in a consolidated environment as application resource needs differ. Furthermore, for multi-tier applications, the amount of resources needed to achieve their QoS goals migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(80 citation statements)
references
References 35 publications
(12 reference statements)
0
71
0
4
Order By: Relevance
“…Unfortunately, only 17% of them have deployed different levels of security solutions for their VDI system. Among the companies who do not have any security solutions, almost half of them agree with that there is no difference of security solutions between virtual server and traditional server, while another 18% of them said that they did not know whether the Application virtualization system changed the security rules (Padala et al, 2007).…”
Section: Security Methodsmentioning
confidence: 99%
“…Unfortunately, only 17% of them have deployed different levels of security solutions for their VDI system. Among the companies who do not have any security solutions, almost half of them agree with that there is no difference of security solutions between virtual server and traditional server, while another 18% of them said that they did not know whether the Application virtualization system changed the security rules (Padala et al, 2007).…”
Section: Security Methodsmentioning
confidence: 99%
“…e theory of control can be used to manage the uncertainty and disruption of a system, described by Maggio et al [32]. Padala et al [33] relied on control theory and discussed CPU utilization. Kamra et al [34] and Liu et al [35] showed resource management efficiency, but not in cloud computing.…”
Section: Related Workmentioning
confidence: 99%
“…The control approach followed in this work is similar to other control theoretic approaches for related problems such as Lim et al (2009Lim et al ( , 2010, Padala et al (2007), except where we have used multiple controllers and a switching methodology. An integral control is utilized, because it removes the steady state errors Lim et al (2009).…”
Section: Control Policymentioning
confidence: 99%